The influence of pretreatment step on hollow braided PET fabric as a potential membrane substrate. (2021) - El-badawy, Tijjani; Hafiz Dzarfan Othman, Mohd; Ridhwan Adam, Mohd; Ismail, A.F.; Rahman, Mukhlis A.; Jaafar, Juhana; Usman, Jamilu; Chinedu Mamah, Stanley; Olabode Raji, Yusuf
Abstract: Self-supporting polymeric hollow fiber membranes prepared using non-solvent induced phase separation (NIPS) often suffer deterioration in mechanical properties due to asymmetric fingerlike and spongelike morphology giving a porous and fragile structure. Hollow braided fibers of Polyethylene terephthalate (PET) have been used as substrate to increase the strength of hollow fiber membranes. However, problems arise from poor interfacial bonding between the braid and coating polymer resulting in peeling off or delamination at the interface. In this work, we report a method of braid treatment and selection with two alkali treatment steps (NaOH and KOH) to study their effect on pure water flux, water contact angle, tensile strength as well as braid morphology of three different braid samples (B1, B2 and B3). B2 sample treated in KOH demonstrated the highest water flux of 1388 L/m 2 h. Examination of surface morphology of the braids revealed a washing effect and enlargement of braid interspaces making them more porous and hence increased permeability, with a contact angle of 0° with water. The sample also exhibited zero weight loss as well as a remarkable tolerance for high temperature with negligible reduction in tensile strength of only about 0.9%. Membrane fabricated with B2-K was demonstrated to have better adhesion between polymer-braid interface in comparison to the control. The pre-treatment step provides a good braid selection basis for onward membrane development with KOH showing the most favorable outcome without losing braid quality.